Embedding CoO nanoparticles in a yolk–shell N-doped porous carbon support for ultrahigh and stable lithium storage. Issue 8 (5th February 2019) - Wang, Shuhai; Teng, Jun; Xie, Yanyu; Wei, Zhang-Wen; Fan, Yanan; Jiang, Ji-Jun; Wang, Hai-Ping; Liu, Heguang; Wang, Dawei; Su, Cheng-Yong
Abstract : CoO/C yolk–shell nanostructures (CoO/C YSNSs) with a unique hierarchical and quasi-homostructural architecture deliver ultrahigh and stable anodic performances for lithium-ion batteries. Abstract : Despite great progress, the development of anode materials with excellent properties for high-performance lithium-ion batteries (LIBs) remains challenging. Rational design and synthesis of novel hybrid nanomaterials that synergistically integrate the structural/compositional advantages of their components provides exciting opportunities and solutions. Here, we demonstrate a dilute atmosphere pyrolysis strategy for the one-step synthesis of a new hybrid nanomaterial, CoO/C yolk–shell nanostructures (CoO/C YSNSs), from a Co-containing metal–organic framework precursor, ZIF-67. The CoO/C YSNSs integrate CoO and carbon into a unique hierarchical and quasi-homostructural architecture, in which both the yolk and shell comprise ultrafine CoO nanoparticles homogeneously embedded in highly porous, conductive and N-doped carbon. Benefiting from such structural and compositional features, CoO/C YSNSs deliver ultrahigh and stable lithium storage performances (retained capacity up to 1970 and 680 mA h g −1 even after 1000 charge/discharge cycles at a current density of 100 and 1000 mA g −1, respectively), and rank among the best cobalt oxide-based anode materials. The formation of CoO/C YSNSs is also investigated and attributed to two synergistic processes of dynamic redox competition and heterogeneous contraction. Our work provides new stimuli to the development of complex hybrid nanostructure-based advanced electrode materials for high-performance batteries.